Ruminococcus gnavus bacteremia, an uncommon presentation of a common member of the human gut microbiota: case report and literature review. Issue 6 (2nd November 2019) - Lefever, Stefanie; Van Den Bossche, Dorien; Van Moerkercke, Wouter; D'Hondt, Mathieu; Alegret Pampols, Maria del Carmen; Struyve, Mathieu; De Bel, Annelies; Boudewijns, Michaël
ABSTRACT: Case report : We present a case of a 66-year-old female diagnosed with  R. gnavus  bacteremia associated with fecal peritonits secondary to small-bowel herniation and perforation. Identification  as  R. gnavus  was delayed because of absence of this species in the MALDI-TOF MS database (Vitek MS, bioMérieux). Identification was provided by 16S rRNA gene sequencing. Review :  R. gnavus,   a Gram-positive, strictly anaerobic bacterium, is a member of the human gut microbiota. Dysbiosis in the gut microbiota, with increased amounts of  R. gnavus,   has been described in inflammatory bowel disease.  R. gnavus  has only been reported occasionally as the cause of infections. Hence the potential pathogenicity is not yet fully recognized, and data regarding the antimicrobial susceptibility profile are rare. Identification of anaerobic bacteria such as  R. gnavus  is greatly accelerated  as a result of the introduction of MALDI-TOF MS. However, as illustrated in this case report, an extensive and up-to-date MALDI-TOF MS database is necessary for providing an accurate identification.